Patched Targeting Peptides for Imaging and Treatment of Hedgehog Positive Breast Tumors. (7th September 2014) - Smith, Daniel; Kong, Fanlin; Yang, David; Larson, Richard; Sims-Mourtada, Jennifer; Woodward, Wendy A.
Abstract : High tumor hedgehog expression is correlated with poor prognosis in invasive ductal carcinoma. Peptides which bind the patched receptor have recently been reported to have a growth inhibitory effect in tumors with activated hedgehog signaling. We sought to examine growth inhibition with these peptides in breast cancer cells and use these peptides as molecular imaging probes to follow changes in hedgehog expression after chemotherapy. Significant growth inhibition was observed in breast cancer cell lines treated with PTCH-blocking peptides. Significant in vitro uptake was observed with both FITC- and 99m Tc-EC-peptide conjugates. In vivo imaging studies displayed greater accumulation of 99m Tc-labeled peptides within tumors as compared to adjacent muscle tissue. Patched receptor expression increased after treatment and this correlated with an increase in tumor radiotracer uptake. These studies suggest that peptides which bind the sonic hedgehog docking site in patched receptor correlate with patched expression and can be used to image patched in vivo . Further, our data suggest that radiolabeled peptides may enable us to examine the activity of the hedgehog signaling pathway and to evaluate response to anti-cancer therapies.